Women of the world : Latin America and the Caribbean - Chaney, Elsa M. (U.S. Department of Commerce Washington, D.C.US, 1984)
Presents and analyzes socioeconomic and sociological statistical data on women in twenty one Latin American and Caribbean Countries. Gives overview of population characteristics of the region. Describes women's literacy and education, their labour force participation, marital status and living arrangements, fertility, and mortality.